Kinetic-Spectrophotometric Determination of Tungsten(VI) Based on Azure I-Ti(III) Reaction in the Presence of Thiocyanate as an Activator - POURREZA*, N.; NIROOMAND, S. (Asian Journal of Chemistry, 2010)
The catalytic effect of tungsten(VI) and activating effect of thiocyanate on the reduction reaction of Azure I by Ti(III) was used to develop a sensitive and rapid kinetic spectrophotometric method for the determination of tungsten(VI). The reaction was monitored spectrophotometrically by measuring the change in absorbance (ΔA) at 646 nm using a fixed time method (2.5 min). The effect of different variables on the reaction was investigated and optimized in order to achieve the highest sensitivity. The calibration graph was linear in the range 5-90 ng mL-1 and the detection limit was 2.9 ng mL-1. The relative standard deviation for ten replicate measurements of 10 and 50 ng mL-1 of tungsten was 4.7 and 3.5, respectively. The method was successfully applied to the determination of tungsten in spring water samples.